B- and T-cell immune responses elicited by the Comirnaty® COVID-19 vaccine in nursing-home residents. (November 2021) - Torres, Ignacio; Albert, Eliseo; Giménez, Estela; Alcaraz, María Jesús; Botija, Pilar; Amat, Paula; Remigia, María José; Beltrán, María José; Rodado, Celia; Huntley, Dixie; Olea, Beatriz; Navarro, David
Abstract: Objectives: The immunogenicity of the Comirnaty® vaccine against coronavirus disease 2019 (COVID-19) has not been adequately studied in elderly people with comorbidities. We assessed antibody and T-cell responses targeted to the S protein of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) following full vaccination in nursing-home residents. Methods: Sixty nursing-home residents (44 female, age 53–100 years), of whom ten had previously been diagnosed with COVID-19, and 18 healthy controls (15 female, age 27–54 years) were recruited. Pre- and post-vaccination blood specimens were available for quantification of total antibodies binding the SARS-CoV-2 S protein and for enumeration of SARS-CoV-2 S-reactive IFN-γ CD4 + and CD8 + T cells by flow cytometry. Results: The seroconversion rate in (presumably) SARS-CoV-2-naïve nursing-home residents (41/43, 95.3%) was similar to that in controls (17/18, 94.4%). A booster effect was documented in post-vaccination samples of nursing-home residents with prior COVID-19. Plasma antibody levels were higher (p < 0.01) in recovered nursing-home residents (all 2500 IU/mL) than in individuals across the other two groups (median 1120 IU/mL in naïve nursing-home residents and 2211 IU/ml in controls). A large percentage of nursing-home residents had SARS-CoV-2 S-reactive IFN-γ CD8 + (naïve 31/49, 63.2%; recovered 8/10, 80%) or CD4 + T cells (naïve 35/49, 71.4%; recovered 7/10, 70%) at baseline, in contrast to healthy controls (3/17, 17.6% and 5/17, 29%, respectively). SARS-CoV-2 IFN-γ CD8 + and CD4 + T-cell responses were documented in 88% (15/17) and all control subjects after vaccination, respectively, but only in 65.5% (38/58) and 22.4% (13/58) of nursing-home residents. Overall, the median frequency of SARS-CoV-2 IFN-γ CD8 + and CD4 + T cells in nursing-home residents decreased in post-vaccination specimens, whereas it increased in controls. Conclusion: The Comirnaty COVID-19 vaccine elicits robust SARS-CoV-2 S antibody responses in nursing-home residents. Nevertheless, the rate and frequency of detectable SARS-CoV-2 IFN-γ T-cell responses after vaccination was lower in nursing-home residents than in controls.